Implementation Of Provision Of Compensation in Improving Employee Performance at PT. Bumi Artha Sedayu Karawang - Rindi Faridhoh; Nandang; July Yuliawati (Institute of Computer Science (IOCS), 2022)
This study aims to determine the implementation of compensation in improving employee performance at PT. Bumi Artha Sedayu Jl Raya Klari no 23-24 East Karawang District. The method used in this research is a qualitative research with triangulation method as a source to analyze using interview, observation and survey instruments. The results of this study indicate that the implementation of compensationprovided for now is still lacking, and performance is still lacking. Pthe company must provide a salary with the Karawang UMR standard, he added in the provision of insurance and to improve employee performance the company must maximize unit sales so that the realization is according to the predetermined target.